Hegel’s Master and Slave Dialectic Yesterday, Today, and Tomorrow: Дијалектиката на Хегел за господарот и слугата вчера, денес и утре - Timofeeva, Oxana; Ruskovska, Rodna (Identities: Journal for Politics, Gender and Culture, 2017)
Author(s): Oxana Timofeeva | Оксана Тимофеева Title (English): Hegel’s Master and Slave Dialectic Yesterday, Today, and Tomorrow Title (Macedonian): Дијалектиката на Хегел за господарот и слугата вчера, денес и утре Translated by (English to Macedonian): Rodna Ruskovska | Родна Русковска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 14, No. 1 (Winter 2017) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 5-26 Page Count: 21 Citation (English): Oxana Timofeeva, “Hegel’s Master and Slave Dialectic Yesterday, Today, and Tomorrow,” Identities: Journal for Politics, Gender and Culture, Vol. 14, No. 1 (Winter 2017): 5-25. Citation (Macedonian): Оксана Тимофеева, „Дијалектиката на Хегел за господарот и слугата вчера, денес и утре“, превод од англиски Родна Русковска, Идентитети: списание за политика, род и култура, т. 14, бр. 1 (зима 2017): 5-26.